2019
DOI: 10.1109/access.2019.2952894
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum Access and Power Control for Cognitive Satellite Communications: A Game-Theoretical Learning Approach

Abstract: With the increasing scarcity of spectrum resources in satellite and terrestrial communications, spectrum sharing becomes a promising option. In this paper, we investigate the spectrum access and power control problem in multibeam-based cognitive satellite communication network. Differ from the most existing spectrum access problems in terrestrial networks, we consider not only the interference between cognitive users, but also the co-channel interference from multi-beam satellite communication system to cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The distance between the transmitter and receiver of each terrestrial cognitive user is set to d = 20m [35]. In all simulations, the transmission loss between terrestrial cognitive users is calculated by ideal attenuation formulation L = 32.5 + 20 lg D (km) + 20 lg F (M Hz), where F is set to 14000 [27]. It is assumed that the cognitive users are interfered by three co-channel beams, the interference coefficient to beam b is set to h = [0.3, 0.2, 0.1], respectively [47].…”
Section: Simulation Results and Behaviormentioning
confidence: 99%
See 4 more Smart Citations
“…The distance between the transmitter and receiver of each terrestrial cognitive user is set to d = 20m [35]. In all simulations, the transmission loss between terrestrial cognitive users is calculated by ideal attenuation formulation L = 32.5 + 20 lg D (km) + 20 lg F (M Hz), where F is set to 14000 [27]. It is assumed that the cognitive users are interfered by three co-channel beams, the interference coefficient to beam b is set to h = [0.3, 0.2, 0.1], respectively [47].…”
Section: Simulation Results and Behaviormentioning
confidence: 99%
“…• It is shown that the joint channel access and power optimization scheme achieves better system throughput performance than only considering channel access, which verifies the effectiveness of the formulated game. It is noted that our earlier work [27] studies the spectrum sharing in cognitive satellite communication in the interweave mode, in which only channel selection is optimized (terrestrial cognitive users are non-cooperative and always transmit with the maximum power), thus significantly reducing the system throughput. Besides, the algorithm proposed in [27] converges slowly and does not always converge to the optimal NE.…”
Section: B Contributionsmentioning
confidence: 99%
See 3 more Smart Citations